Meningkatan Hasil Belajar Siswa Materi Pokok Pasar Monopoli, Monopolistik Dan Oligopoly Melalui Media Gambar Dengan Model Pembelajaran Examples Non Examples Pada Mata Pelajaran Ekonomi Bisnis Kelas X Otomatisasi Dan Tata Kelola Perkantoran SMK Negeri 8 Samarinda - Sri Kuntari (Lembaga Pengembangan Kinerja Dosen, 2022)
The problem in this study is the low quality of learning Business Economics class X Office Automation and Governance, which is known from the average student learning outcomes in the subject of Business Economics only reaching 67.43, in other words it has not reached the specified KKM, which is equal to 78, this is due to the lack of use of media images with learning models in the teaching and learning process, lack of student interest, and low student learning outcomes in learning Business Economics. Therefore, this research discusses the use of media images with the Examples Non Examples learning model to improve student learning outcomes in class X Business Economics Automation and Office Management at SMK Negeri 8 Samarinda. This study uses the Classroom Action Research (PTK) method, the research procedure used is in the form of cycles and each cycle is carried out through four stages, namely: planning, implementing, observing, and reflecting. The data collection technique was carried out using qualitative techniques, while the data collection tool used was a question instrument. The subjects of this study were class X students of Office Automation and Governance at SMK Negeri 8 Samarinda with a total of 35 students. The results showed that the use of media images with the Examples Non Examples learning model can improve student learning outcomes in learning Business Economics. This can be seen from the completeness of student learning outcomes in the pre-cycle, namely 18 students (51.43%), there was an increase in cycle I, namely 27 students (77.14%) and in cycle II it increased to 35 students (100%). Based on the results of the study, it can be concluded that the use of media images with the Examples Non Examples learning model can improve student learning outcomes in the subject of Business Economics class X Office Automation and Management at SMK Negeri 8 Samarinda.